PREPOSITION ERRORS IN @BARACKOBAMA’S CAPTION OF INSTAGRAM POSTS - Ruri Fadhilah Kurniati; Amelia Panji Sekar Pameling (ETNOLINGUAL, 2023)
The purpose of this study is to identify the prepositional errors that are made in the captions of @barackobama’s Instagram posts. This study employed a qualitative descriptive research methodology. The data in this study is 167 post captions of @barackobama Instagram accounts during 2022. Based on Azar’s (2006) prepositional theory, this study finds 2 prepositional errors, which is equal to 1,2%, in two different captions. The errors are preposition of time and preposition of place. The results of this study differ from those of Dwiyanti (2017) and Putri (2019). They found more errors than the number of errors in this study. The difference in the number of errors found can be because the subjects of their study are Indonesian students who are English foreign language learners. While the subject of this study is an English native speaker. The captions of the Instagram posts @barackobama are highly recommended for students to learn English.